PEMANFAATAN CENDAWAN Beauveria bassiana(BALS.) VUILL. SEBAGAI MIKO-INSEKTISIDA TERHADAP KUTU LONCAT JERUK Diaphorina citri KUW. (HEMIPTERA: LIVIIDAE) - Muhammad Agung Permadi (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
Asiatic citrus psyllid Diaphorina citri Kuwayama has been considered as one of important citrus pests and a vector of a serious citrus disease as well, greening disease or known as Huanglongbing (HLB). Among entomophatogenic fungi which can be used to control those pest insects isBeauveria bassiana.The objective of this study was to measure the infectivity ofB. bassianaagainst adult of D. citri.B. bassianaconidia that used were 103, 104, 105, 106, 107, and 108conidia/ml.The experiment was repeated three times and arranged in a completely randomized design (CRD). Mean was analized by Duncan's multiple range test correction at the level α=0.05. B. bassianacaused mortality of D. citriat rate of 10%, 15%, 18.33%, 26.67%, 33.33% and 53.33% respectively. The result showed that LC50 of B. bassianawas 1.52 x 108conidia/ml.